DANCE AS PHYSICAL THERAPY RESOURCES IN THE REEDUCATION PSYCHOMOTOR AT PATIENT WITH SPECIAL NEEDS (Fiep Bulletin - online, 2012)
This study aims to verify the effectiveness of dance as a physical therapy resource in psychomotor rehabilitation in individuals with special needs. The sample consisted of people with mental disabilities which was assessed by the Scale of Motor Development (EDM) including fine motor (MF), overall motility (MG), the body schema (EC), the spatial organization (SO), temporal organization (OT) and equilibrium (EQ). Then the subjects were divided into two groups, with 14 in the control group and 18 in group dance, which participated in 20 sessions with dance activities. The results showed statistically significant changes from the general motor age (IMG) and General Motor Quotient (MGQ) of the dance group. It is concluded that the use of dance as a physical therapy resource wich results in improved psychomotor aspects.